Kesiapan Guru dalam Implementasi Kurikulum Merdeka di SMKN Se-Kota Pariaman - Lestari, Anggun Mawar; Gistituati, Nurhizrah (Global Action and Education for Society, 2024)
This research is based on the author's observations regarding Teacher Readiness in Implementing the Independent Curriculum in Vocational Schools throughout Pariaman City with the aim of exploring information about teacher readiness in planning, implementing and evaluating learning based on the independent curriculum in terms of the aspects of teacher knowledge, understanding and skills. This type of research is quantitative descriptive. The population of this research is all teachers in SMKN throughout Pariaman City totaling 241 teachers with a research sample of 153 teachers taken based on the Stratified Proportional Random Sampling technique. Before being used for research, the questionnaire was tested for validity and reliability assisted by the SPSS version 29 program. The data analysis technique uses the average formula (mean). The results of the research show that teacher readiness in implementing the independent curriculum, in terms of (1) learning planning with an average of 3.63 and TCR (72.6%) has quite good criteria, (2) implementation of learning with an average of 3.82 and TCR (76.4%) has quite good criteria, (3) learning evaluation with an average of 3.75 and TCR (75%) has quite good criteria.